2016
DOI: 10.1002/ddr.21319
|View full text |Cite
|
Sign up to set email alerts
|

Novel 5‐Hydroxy, 5‐Substituted Benzenesulfonamide Pyrimidine‐2,4,6‐Triones Attenuate Lipopolysaccharide‐Induced Acute Lung Injury via Inhibition of the Gelatinases, MMP‐2 and MMP‐9

Abstract: Preclinical Research A novel series of ten 5-hydroxy, 5-substituted benzene sulfonamide pyrimidine-2,4,6-triones were synthesized and their structures ascertained using (1) H-NMR, (13) C-NMR, mass and elemental analysis. These compounds were subsequently tested for inhibition of MMP-2 and MMP-9 where most exhibited activity with compound 5i being the most potent against MMP-2 and MMP-9 with IC50 values of 2.35 nM and 8.24 nM, respectively. Compound 5i was further analyzed in a mouse LPS-induced acute lung inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…An increase in MMP-9 expression in animal models and clinical patients is a common pathophysiological manifestation of lung injury caused by various factors and, therefore, MMP-9 was hypothesized to serve an important role in the development of lung injury (16,17). Analysis of candidate pathways mediating MMP-9 upregulation in ALI demonstrated that an increased level of MMP-9 in lung tissue corresponded with more severe lung injury (16).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in MMP-9 expression in animal models and clinical patients is a common pathophysiological manifestation of lung injury caused by various factors and, therefore, MMP-9 was hypothesized to serve an important role in the development of lung injury (16,17). Analysis of candidate pathways mediating MMP-9 upregulation in ALI demonstrated that an increased level of MMP-9 in lung tissue corresponded with more severe lung injury (16).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the presence of electron donating group produced a detrimental effect on the inhibition activity (Nicolotti et al, 2012). in vivo investigations on animal models with lipopolysaccharide induced acute lung injury displayed a reversal of inflammatory cell infiltration and tissue damage in the presence of barbiturate derivatives 9 , 10 (Figure 2) (He et al, 2016). Hence, the barbiturate derivatives presented a highly desirable profile for targeting matrix‐metalloproteinases.…”
Section: Barbiturate Derivatives For Targeting Matrix Metalloproteinasesmentioning
confidence: 99%